Model Matematika Panel Surya Satelit Komunikasi Orbit Rendah Ekuatorial Menggunakan Simulink - Desti Ika Suryanti; Ahmad Fauzi (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2022)
Solar cells or photovoltaic is a renewable energy source as a generator of electrical energy that is able to convert solar energy into electrical energy. Solar cells consist of series and parallel arrangement to form a solar panel. Solar panel technology is widely used, one of which is space technology, especially satellite technology. Solar cells use in satellites generates energy required for the satellite operation. To design the arrangement of solar cells based on the expected power and or the power produced, one of them is using mathematical modeling methods; The mathematical model of solar panels is developed and presented in this paper using the Matlab-Simulink GUI application. This mathematical model was developed using the basic circuit equations of a solar cell including the effects of solar irradiance and temperature changes. Based on the modeling, the output characteristic curve of the model is obtained according to the characteristics of each solar panel of the equatorial low orbit communication satellite. The power generated by the solar panel will increase when the solar irradiance increases at a constant temperature. When the temperature decreases and the solar irradiance remains constant, the output power and voltage increase slightly while the output current approaches a constant.